Research and Application of Signal Acquisition Algorithm for Beidou Navigation System - Xinmiao Liao; Ling Lin; Xingqi Jiang (IEEE Access)
With the increasing diversification of functions of the BeiDou navigation system, the accuracy of signal capture has a greater impact on the receiver. At present, many signal capture methods suffer from high latency and unstable accuracy. To address this issue, research proposed combining the fast Fourier transform algorithm with an improved time-domain parallel signal capture method, and applying the method to field programmable gate array simulation applications. The results showed that the proposed method had a maximum capture intensity of 86.7 and a minimum intensity of 18.9 for the signal in section A. The maximum strength of the un-captured signal was 40, and the minimum strength was 3. This denoted that the proposed method performed well in capturing signals for complex road conditions. The method proposed by the research had a maximum capture intensity of 86.7 and a minimum intensity of 18.9 for the signal in section B. The maximum strength of the un-captured signal was 40, and the minimum strength was 3. This value indicated that the signal quantity not captured by the proposed method was lower than the signal quantity already captured. From the above, the proposed method can efficiently and accurately capture various satellite signals, with stable capture effects, which provides effective technical support for the construction of global satellite navigation systems.